(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2020)
This issue represents a more diverse group of scholars. The six standard articles, ten peer reviewed essays, and one book review are from scholars in Botswana, Canada, Ecuador, Finland, Nepal, South Africa, Turkey, and the United States. They cover a wide range of issues from curriculum to institutional and global perspectives, from bias to inclusion and justice in higher education, from academic leadership and good governance to international education, from virtual learning and innovation in education. Many directly focus on issue about or raised by the ongoing pandemic. We hope that you will find a few articles worth browsing and skimming through, with one or more to read closer.